Regional-scale groundwater flow and salt transport models for exploring agro-environmental remediation strategies in an irrigated river valley - Morway, Eric D., author; Gates, Timothy K., advisor; Labadie, John W., committee member; Baù, Domenico A., committee member; Ronayne, Michael J., committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: irrigation; salinization; waterlogging; water markets; agriculture